2016
DOI: 10.15761/ohns.1000134
|View full text |Cite
|
Sign up to set email alerts
|

Development and clinical evaluation of bipolar radiofrequency cryptolysis

Abstract: Objectives: Cryptolysis is a highly efficient conservative procedure in halitosis caused by deep tonsillar crypts or tonsilloliths. It can be carried out by laser, coblation or radiofrequency application, with radiofrequency application being the most cost effective. Monopolar methods generate a wider electrical field with more side effects; therefore, it is necessary to develop and test a new bipolar electrode. Methods:In a prospective non-randomized study seventy-one patients were treated with a monopolar pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…RF application with bipolar and monopolar rods have been studied several times. RF cryptolysis targeted to destruct the epithelium with the formation of fibrosis which tends to close the crypt openings (10,14,21,22). Vogt et al reported that the RF cryptolysis is a day case procedure that is minimally invasive with lower complaint rates, bipolar RF cryptolysis can cause less pain than the monopolar technique also.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…RF application with bipolar and monopolar rods have been studied several times. RF cryptolysis targeted to destruct the epithelium with the formation of fibrosis which tends to close the crypt openings (10,14,21,22). Vogt et al reported that the RF cryptolysis is a day case procedure that is minimally invasive with lower complaint rates, bipolar RF cryptolysis can cause less pain than the monopolar technique also.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, it is indicated that laser cryptolysis has higher costs though it has a faster healing period with less postoperative pain, immediate return to normal dietary habits, and fewer complication rates (10,22). RF ablation costs are reported as less than laser cryptolysis and suggested as it can be more appropriate for the patients who have insufficient mouth opening and too much gag reflex (14). Our patients showed no significant gag reflex after applying lidocaine spray and DOI: 10.33808/clinexphealthsci.873557…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vogt et al [9] presented their results of bipolar radiofrequency cryptolysis in hypertrophic tonsillar tissue and claimed that bipolar technique showed better results when compared to the monopolar method, with emphasis on the fact that lesser lateral heat damage around the bipolar electrodes could be achieved resulting in a hypothetic minor reaction of the tonsillar tissue; however, their results were not supported by a cohort study. Identical results have been observed in bipolar and monopolar applications for the reduction of the lower turbinates, where the energy was delivered by a bipolar double-needle electrode and the epithelium would be preserved, whereas monopolar usagealso known as so-called "coblation tunneling" leads to histological changes similar to CO2 laser therapy involving the transformation of columnar epithelium into cuboidal or squamous epithelium due to inevitable burn injury.…”
Section: Discussionmentioning
confidence: 99%